Influenza vaccination and the 'diversity paradox' - Craig P. Thompson; Uri Obolski (Taylor & Francis Group, 2018)
The antigenic evolution of influenza is widely assumed to occur by antigenic drift, in which strains incrementally acquire mutations in highly variable epitopes under strong immune selective pressure, such as those in the major influenza antigen haemagglutinin. However, this is not easy to reconcile with epidemiological observations, which show that each influenza season is dominated by a limited number of strains. Here, we discuss this paradox in light of recent influenza epidemics that have been characterised by low vaccine effectiveness and dominated by strains of limited antigenic and genetic diversity.